2006
DOI: 10.1007/s10067-006-0286-2
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary involvement in ankylosing spondylitis

Abstract: This is a prospective study analyzing 52 asymptomatic, consecutive patients with ankylosing spondylitis (AS), who submitted to a pulmonary investigation that included plain chest radiography, pulmonary function test (PFT), and thoracic high-resolution computed tomography (HRCT). The results were compared according to sex, race, dorsal spine involvement, thoracic diameter, smoking status, and HLA-B27. There were four patients (8%) with an altered plain chest radiograph. PFT presented a restrictive pattern in 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 29 publications
4
49
2
3
Order By: Relevance
“…Although early pulmonary lesions were also detected in this study group, HRCT abnormalities were more frequent in late AS patients. As it is well demonstrated that HRCT is more sensitive than the chest X-ray in detecting lung parenchyma changes in patients with AS [17,20,21,32,34], we did not compare the plain radiography and HRCT findings in this study.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Although early pulmonary lesions were also detected in this study group, HRCT abnormalities were more frequent in late AS patients. As it is well demonstrated that HRCT is more sensitive than the chest X-ray in detecting lung parenchyma changes in patients with AS [17,20,21,32,34], we did not compare the plain radiography and HRCT findings in this study.…”
Section: Discussionmentioning
confidence: 74%
“…Altin et al [21] compared early and late pleuropulmonary findings, and they observed that even radiological findings were more prominent in late AS (16 of 20 patients); 11 of 18 patients with early AS (disease duration\10 years) had abnormal HRCT findings. Finally, Sampaio-Barros et al [34] showed HRCT abnormalities in 40% of 52 patients, presenting non-specific parenchymal opacities (19%) as the most common type of involvement. In summary, HRCT changes were found to be prevalent in AS even in patients with early disease, and in those with normal chest radiographs and without respiratory symptoms [35,36].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In previous studies, which were made with reontgenographic evaluation, pulmonary involvement frequency was reported between 1 to 15% in AS in different studies (Rosenow et al 1977;Fenlon et al 1997). However in recent studies, which were performed with chest high resolution computed tomography, the pulmonery involvement freguency was reported between 40 to 80% in different studies Turetschek et al 2000;Kiris et al 2003;Senocak et al 2003;Souza et al 2004;Sampaio-Barros et al 2007). The pulmonary involvement in AS usually emerges either in the form of interstitial lung disease or in the form of restricted pulmonary functions due to chest wall limitation.…”
Section: Clinical Assessments and Laboratory Parametersmentioning
confidence: 99%
“…Ali i rad u kućnim uslovima je bolji od odsustva bilo kakvog programa vježbi, zaključili su u svom radu Lopes i saradnici [13]. Bolesnicima sa ankilozirajućim spondilitisom se preporučuje plivanje i hodanje, i ispitivanje koje su proveli Sampai-Barros i saradnici [14] pokazalo je da su boelsnici koji su kombinovali i jedno i drugo imali bolju toleranciju na vježbe i bolji pulmonalni kapacitet od onih koji su imali samo jedan oblik aktivnosti. Zato su plivanje i hodanje navedeni kao korisni oblici aerobnog treninga za bolesnike sa ankilozirajućim spondlitisom [14].…”
Section: Diskusijaunclassified